2000
DOI: 10.1097/00003246-200007000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 reduces myocardial reperfusion injury by inhibiting proinflammatory cytokines production during cardiac surgery

Abstract: PGE1 suppressed the production of IL-6 and IL-8 but not IL-10, IL-1ra, sTNF RI, or sTNF RII. The change in the balance between pro-and anti-inflammatory cytokines may be one of the most important cytoprotective mechanisms of PGE1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…After histological analysis according Chiu et al 20 it was demonstrated that without PTX 1,13,14,16 and PGE1 [17][18][19][20] The PGE1 [17][18][19], is known by its intense vasodilator effect, for being a substance with intense biological activity that has been used for such a longtime to treat. the chronic arterial occlusive disease, since beside to vasodilation capacity it also inhibit platelets aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After histological analysis according Chiu et al 20 it was demonstrated that without PTX 1,13,14,16 and PGE1 [17][18][19][20] The PGE1 [17][18][19], is known by its intense vasodilator effect, for being a substance with intense biological activity that has been used for such a longtime to treat. the chronic arterial occlusive disease, since beside to vasodilation capacity it also inhibit platelets aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the ischemic effects on cells many types of drugs have been used during intestinal reperfusion as pentoxyflline 16 (PTX) and prostaglandin E1 (PGE1) 17 , in the ischemic-reperfusion process (I/R). PTX has antioxidant action inhibiting directly the anion superoxide, which indirectly blocks the action of the enzyme xanthine-oxidase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical manifestation of SIRS following CPB is mediated via cell-derived cytokines that target end-organ receptors. After CPB, elevated serum levels of the pro-inflammatory cytokines, tumor necrosis factor (TNF)-a, interleukin (IL)-6 and IL-8, as well as the anti-inflammatory cytokine IL-10 have been found 2,3 . The potent vasodilator nitric oxide (NO) has also been implicated in SIRS pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Kawamura et al (2000) reported that PGE1 reduced myocardial reperfusion injury by inhibiting proinflammatory cytokine productions, including IL-6 and IL-8, during cardiac surgery. Here we demonstrated that lipo-PGE1 suppressed the productions of serum IL-6 and TNF-α after myocardial infarction reperfusion.…”
Section: Fig 2 Excised Heart Stained With Evans Blue Dye and Thioflamentioning
confidence: 99%